Customer Satisfaction Analysis of Bakerzin Pondok Indah that Affected Quality Product, Service Quality, Servicescape with Price Preception as Mediation Variables - Irmi Dayana; Aris Budiono (International Economic and Finance Review, 2022)
This study aims to determine the effect of product quality, service quality, and Servicescape on customer satisfaction through the perception of prices in Bakerzin restaurants. Data collection was carried out in April 2022 by conducting a survey of 120 respondents with 20 respondents for validity and reliability testing and 100 respondents for path test analysis, sampling using the Roscoe technique, all of which were visitors to Bakerzin Restaurant using path analysis techniques to see the direct and indirect paths as dependent variables on the independent variables. This study resulted in the following conclusions: product quality has a significant effect on perceived prices, service quality has no significant effect on perceived prices, Servicescape has a significant effect on perceived prices, product quality has no significant effect on customer satisfaction, perceived prices have a significant effect on customer satisfaction, quality service has a significant effect on customer satisfaction, Servicescape has no significant effect on customer satisfaction, product quality has no significant effect on price perception through customer satisfaction, service quality has a significant effect on price perception through customer satisfaction. Servicescape has no significant effect on Price Perception through Customer Satisfaction. Keywords: Product Quality, Service Quality, Servicescape, Price Perception, Customer Satisfaction.